MXene / silicon composite material, preparation thereof and application of MXene / silicon composite material as negative electrode of lithium ion battery

By introducing metal catalysts between the MXene material layers and deposition of silane by CVD method, MXene/silicon composite material was prepared, which solved the problem of electrochemical performance deterioration caused by the volume effect of silicon negative electrode materials in lithium-ion batteries, and achieved higher cycle stability and electrochemical performance.

CN119812245AActive Publication Date: 2025-04-11ZHEJIANG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411841418.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-11
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

During the circulation process, the silicon negative electrode material in existing lithium-ion batteries will cause the electrolyte interface to rupture and repetitive growth due to volume effects, resulting in increased battery impedance and deterioration of electrochemical performance.

Method used

By introducing a metal catalyst between the MXene material layers, the silane is decomposed and deposited between the MXene layers by chemical vapor deposition (CVD) method to prepare an MXene/silicon composite material, effectively anchoring the silicon material to the MXene layer, limiting the volume effect of silicon.

Benefits of technology

This method effectively suppresses the volume effect of silicon negative electrode material, improves its cycle stability and electrochemical performance, and significantly improves the energy density of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005188051270000011
    Figure HDA0005188051270000011
  • Figure HDA0005188051270000012
    Figure HDA0005188051270000012
  • Figure HDA0005188051270000021
    Figure HDA0005188051270000021
Patent Text Reader

Abstract

The invention discloses an MXene / silicon composite material, preparation thereof and application of the MXene / silicon composite material as a negative electrode of a lithium ion battery. The preparation method of the MXene / silicon composite material comprises the following steps: (1) obtaining an MXene material; (2) obtaining an MXene material solution of a cationic surface active agent intercalation layer; (3) adding a metal soluble salt into the cationic surfactant intercalated MXene material solution to obtain a metal intercalated MXene material; and (4) carrying out high-temperature treatment on the metal intercalation MXene material in a protective atmosphere to activate metal, introducing silane-containing gas at a high temperature, carrying out heat preservation treatment, and cooling to room temperature to obtain the MXene / silicon composite material. The invention provides application of the MXene / silicon composite material as a lithium ion battery negative electrode material, the prepared composite material can limit the volume effect of a silicon negative electrode, the capacity of the lithium ion battery negative electrode material is greatly improved, and the cycle performance is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

(I) Technical field

[0001] The invention relates to a MXene / silicon composite material and its preparation and application as a negative electrode of a lithium ion battery. (II) Background technology

[0002] The rapid development of electric vehicles, clean energy storage and portable electronic products has put forward higher requirements for the energy density of secondary batteries. The improvement of energy density depends on the performance of electrode materials. At present, the theoretical capacity of commercial graphite negative electrode materials in lithium-ion batteries is only 372mAh / g, while the energy density of power batteries built with graphite as negative electrode materials is difficult to exceed 300Wh / kg. Therefore, it is urgent to research and develop new high-capacity negative electrode materials.

[0003] Silicon has attracted extensive attention from researchers because of its high theoretical capacity (4200mAh / g). However, during the battery cycle, the silicon negative electrode will react with lithium to produce a serious volume effect, resulting in a volume expansion of up to 300%. This will cause the solid electrolyte interface (SEI) generated between the electrolyte and the silicon-based interface to continuously rupture and grow repeatedly, continuously consume the electrolyte, increase the battery impedance, and ultimately deteriorate the electrochemical performance of the battery. Therefore, in previous studies, researchers first curbed the volume effect by reducing the volume of silicon particles and explored different nano-preparation methods. The prepared silicon nanoparticles, silicon nanowires, silicon nanotubes, and silicon nanoporous structures all have good electrochemical properties. Secondly, by doping a small amount of silicon and graphite, the tap density of the silicon-based negative electrode is increased, the low electronic conductivity of the silicon-based negative electrode is improved, and the harm caused by the volume effect is weakened through the gaps between graphite layers. Finally, the researchers used a variety of new carbon materials to composite with silicon-based materials, such as graphene, carbon nanotubes, porous carbon microspheres, MXene, etc. When composited with silicon-based materials, these new carbon materials can effectively improve the defects of silicon negative electrodes, thereby giving silicon-based negative electrodes excellent electrochemical properties. Among them, the most special carbon material is MXene material, which is a class of two-dimensional inorganic compound materials composed of transition metal carbides, nitrides or carbonitrides with a thickness of several atomic layers. The MAX phase, the precursor of the MXene material, can be used to obtain MXene materials with different surface groups and different shapes ("accordion-shaped", flaky, layered, etc.) by using different etching methods or selecting different etchants. Therefore, MXene materials are widely used. MXene materials have good conductivity and strong mechanical strength, and their unique lamellar structure can effectively suppress the volume effect of silicon negative electrodes. However, the silicon-based and MXene composite negative electrodes currently developed basically use physical composites such as electrostatic adsorption and spray drying, or simple mixing processes such as ball mills and stirrers. The interaction and binding force between silicon and MXene are not strong, and the confinement effect of MXene lamellae is greatly weakened, resulting in its electrochemical performance still needs to be improved.

[0004] With the increasing research on the preparation of silicon-carbon anode by chemical vapor deposition, a new direction has been provided for the preparation of MXene / silicon composite materials. Chemical vapor deposition (CVD) technology is usually used in the surface modification process of materials, aiming to use gaseous substances on the surface of materials to react chemically at a certain temperature and generate a solid deposited film. Due to the activity and tinyness of gas molecules, they can achieve structural regulation that cannot be achieved by conventional physical composite methods. As mentioned above, the unique layered structure of MXene materials has nanopores that can limit the volume effect of silicon anodes. However, conventional composite methods cannot penetrate into its interlayers and cannot make MXene materials play a confining role in silicon anodes. Therefore, using gaseous silicon-based precursors, silicon-based materials can be anchored into the nano-voids and pores of MXene materials to achieve true confinement and improve the electrochemical performance of MXene / silicon composite materials. (III) Summary of the invention

[0005] In view of a series of problems existing in silicon negative electrodes, the present invention aims to provide a MXene / silicon composite material and a preparation method thereof and application as a negative electrode material for lithium-ion batteries.

[0006] To achieve the purpose of the present invention, the technical solution of the present invention is described below:

[0007] In a first aspect, the present invention provides a method for preparing a MXene / silicon composite material, wherein a metal catalyst is introduced between MXene layers, and a MXene / silicon composite material is prepared by a CVD method through decomposition and deposition of different metal-catalyzed silanes between MXene layers. The preparation method comprises the following steps:

[0008] (1) Taking MAX raw materials and treating them in a hydrofluoric acid solution to obtain MXene materials;

[0009] (2) immersing the MXene material obtained in step (1) in a solution containing a cationic surfactant content of 0.001-20 g / mL, stirring at 20-100° C. for 0.5-72 h to obtain a MXene material solution intercalated with a cationic surfactant;

[0010] (3) adding a metal soluble salt to the cationic surfactant intercalated MXene material solution obtained in step (2), stirring at 20-100° C. for 0.5-72 h, and then centrifuging, washing, and drying to obtain a metal intercalated MXene material;

[0011] (4) The metal intercalation MXene material obtained in step (3) is heated to 300-1000°C at a rate of 1-10°C / min under a protective atmosphere, and kept warm for 0.1-12h to activate the metal and activate its catalytic effect, then cooled to 200-800°C, and a gas containing silane is introduced at a flow rate of 0.01-5L / min for 1-240min, and then kept warm for 0.1-12h, and finally cooled to room temperature at a rate of 1-20°C / min to obtain a MXene / silicon composite material.

[0012] In step (1) of the present invention, the MXene material can be Ti3C2, Ti2C, Ti4C3, Ti2N, Nb2C, Nb4C3, Ta2C, Ta4C3, V2C, V3C2, V2N, Cr2C, Cr3C2, Zr3C2, Hf3C2, Mo2C, Mo2N, W2N, Cr2TiC2, Mo2TiC2, Mo2Ti2C3, TiNbC or Ti3CN. Those skilled in the art can select suitable MAX raw materials according to the MXene materials to be prepared, and prepare MXene materials by methods reported in the literature. Preferably, the specific operation of step (1) is: weighing the MAX raw material, adding it to a HF solution with a mass fraction of 10 to 50%, wherein the amount of HF solution added is 3 to 50 mL / g based on the mass of the MAX raw material, soaking at room temperature for 2 to 56 hours (more preferably 24 to 36 hours), then centrifuging, washing with water to pH = 6 to 7, and drying to obtain MXene powder.

[0013] In step (2) of the present invention, the cationic surfactant is one of decanyltrimethylammonium bromide, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide or any combination thereof, and preferably has a purity greater than 90%. The concentration of the cationic surfactant in the solution is preferably 0.001-0.5 mol / L, more preferably 0.005-0.3 mol / L. The amount of the solution containing the cationic surfactant is 5 to 1000 mL / g, preferably 50 to 500 mL / g, based on the mass of the MXene material. The stirring in step (2) is preferably carried out at 30-80°C, more preferably at 30-65°C, and further preferably at 30 to 50°C, and the stirring time is preferably 1-36h, more preferably 3 to 24h, and further preferably 10 to 24h.

[0014] In step (3) of the present invention, the metal soluble salt is a soluble salt containing at least one of the elements iron, cobalt, nickel, lead, copper, aluminum, antimony, manganese, tin, zinc, molybdenum, vanadium, zirconium and tungsten, and the soluble salt can be a metal chloride, nitrate, sulfate or acetate; preferably, the purity of the metal soluble salt is greater than 90%. The added concentration of the metal soluble salt is 0.001 to 1 mol / L. Further, the stirring in step (3) is preferably carried out at 20-70°C, more preferably at 20-60°C, and the stirring time is preferably 1-36h, more preferably 5 to 24h.

[0015] In step (4) of the present invention, the gas containing silane is a mixed gas of silane and other gases, and the other gases are one or a mixture of any of argon, nitrogen and hydrogen. Preferably, the purity of argon, nitrogen and hydrogen is greater than 90%, and the purity of silane is also preferably greater than 90%. In the gas containing silane, the volume ratio of silane to other gases is preferably 10-30%:90-70%, more preferably 10-20%:90-80%, and most preferably 10%:90%.

[0016] In step (4) of the present invention, the metal intercalation MXene material is preferably first heated to 400-1000°C at a rate of 2-8°C per minute under a protective atmosphere and kept warm for 1-12 hours to activate the metal and activate its catalytic properties. The temperature is further preferably 400-900°C, most preferably 500-800°C, and the holding time is preferably 1-8 hours, most preferably 1-6 hours. Subsequently, the temperature is lowered to 200-800°C, preferably 300-800°C, and most preferably 400-700°C. The flow rate of the silane-containing gas is 0.01-5L / min, preferably 0.1-3L / min, and most preferably 0.1-2L / min. The time for passing the silane-containing gas is 1-240min, preferably 1-180min, and most preferably 1-120min. Then, the mixture is kept warm for 0.1-12h, preferably 0.1-10h, and most preferably 0.5-6h. Finally, the mixture is cooled to room temperature at a rate of 1-20°C / min. The preferred cooling rate is 1-15°C / min, and the most preferred cooling rate is 1-10°C / min.

[0017] The method for preparing the MXene / silicon composite material of the present invention preferably consists of steps (1) to (4).

[0018] In a second aspect, the present invention provides a MXene / silicon composite material prepared according to the preparation method described in the first aspect.

[0019] In a third aspect, the present invention provides the use of the MXene / silicon composite material as a negative electrode material for a lithium-ion battery.

[0020] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:

[0021] (1) The preparation method of the present invention is highly efficient and feasible. By utilizing the negatively charged surface of MXene materials after HF acid etching, cationic surfactants are inserted into the interlayers of MXene materials through electrostatic interaction, and then metals are intercalated into the interlayers of MXene by ion exchange. The metals between MXene layers are activated by high-temperature activation, which helps the subsequent catalytic decomposition and deposition of silane between MXene layers.

[0022] (2) The MXene / silicon composite material prepared by the present invention is used as a negative electrode material for lithium-ion batteries. During the charge and discharge process, the MXene interlayer confinement can effectively suppress the volume effect of silicon, and effectively improve the cycle stability of silicon negative electrode materials while providing high capacity. The electrochemical performance of the MXene / silicon composite material prepared by this method is significantly better than that of the MXene / silicon composite material prepared by conventional methods. (IV) Description of the drawings

[0023] Figure 1 This is the EDS image of silane deposited on the MXene material after Sn metal catalysis by CVD process in Example 1. It can be seen from the image that there are abundant silicon nanoclusters inside and on the surface, and the CVD deposition effect is good.

[0024] Figure 2 This is a SEM picture of silane deposited on the MXene material after Sn metal catalysis through the CVD process in Example 1.

[0025] Figure 3 This is a TEM image of silane deposited on the MXene material after Sn metal catalysis through the CVD process in Example 1.

[0026] Figure 4 This is a lithium-ion battery cycle performance diagram of Example 1 in which silane is deposited on a MXene material after Sn metal catalysis through a CVD process, as well as a lithium-ion battery cycle performance comparison diagram with the MXene material.

[0027] Figure 5 This is a lithium-ion battery cycle performance diagram of Example 2 in which silane is deposited on a MXene material after Zn metal catalysis through a CVD process, as well as a lithium-ion battery cycle performance comparison diagram with the MXene material. (V) Specific implementation methods

[0028] The technical solution of the present invention is further described below with reference to specific embodiments, but the protection scope of the present invention is not limited thereto.

[0029] Example 1

[0030] Take 2g Ti3AlC2 powder (MAX) into a beaker, add 80mL HF (20%) solution, stir, and soak and etch at room temperature for 24h. Then centrifuge the etched Ti3C2 MXene powder, wash with deionized water to pH = 6-7, and freeze-dry in a freeze dryer for 12h. Stir 0.1g of the dried Ti3C2 MXene powder in 40mL of an aqueous solution containing 0.005mol / L hexadecyltrimethylammonium bromide (CTAB) at 40°C for 18h. Then add 0.1mol / L tin tetrachloride and stir at 40°C for 16h, wash with deionized water, and dry. The dried sample was placed in a CVD furnace and heated to 500°C at a rate of 5°C per minute under the protection of nitrogen, then kept warm for 2 hours to activate the Sn metal, then cooled to 400°C and introduced a mixed gas of silane and argon for 30 minutes, with a volume ratio of 10%:90% and a flow rate of 0.1 liter per minute. The introduction time was 20 minutes, and then kept warm for 1 hour. Finally, it was cooled to room temperature at a rate of 5°C per minute to obtain a MXene / silicon composite material.

[0031] The MXene / silicon composite material prepared in Example 1 was used to make an electrode in the following manner.

[0032] MXene / silicon composite material: carbon black: CMC were weighed in a mass ratio of 80:10:10, ground evenly and mixed with water to prepare a slurry, which was then coated on a copper current collector to make an electrode. The metal lithium sheet was used as the counter electrode, the electrolyte was 1 mol / L LiPF6+DEC / EC (1:1)+10% FEC (vol%), and a polycarbonate film was used as a separator to assemble a simulated lithium-ion battery. Figure 4 The cyclic performance curve of the corresponding battery at a current density of 100 mA / g and a voltage range of 0.01–1.5 V indicates that the measured battery has a high capacity and good cyclic performance at a current density of 100 mA / g. It can be seen that the discharge capacity of the MXene / silicon composite material prepared in Example 1 after 100 cycles at a current density of 100 mA / g is close to 600 mAh / g ( Figure 4 ), compared with the capacity of ordinary Ti3C2 MXene materials (~150mAh / g), the capacity has been greatly improved, and the cycle performance is relatively excellent.

[0033] Example 2

[0034] Take 4g Ti3AlC2 powder (MAX) into a beaker and add 60mL HF (25%)

[0035] Solution, stir, soak and etch at room temperature for 36 hours. Then centrifuge the etched Ti3C2 MXene powder, wash with deionized water to pH = 6-7, and freeze-dry in a freeze dryer for 12 hours. Stir 0.5g of dried Ti3C2 MXene powder in 60mL of an aqueous solution containing 0.03mol / L dodecyltrimethylammonium bromide (DTAB) at 30°C for 20 hours. Then add 0.1mol / L zinc acetate and stir at 40°C for 20 hours, wash with deionized water, and dry. The dried sample is placed in a CVD furnace and heated to 600°C at a rate of 5°C per minute under the protection of nitrogen, then kept warm to activate Zn metal for 3 hours, then cooled to 500°C and passed 60min of silane and nitrogen mixed gas, with a volume ratio of 10%:90%, a flow rate of 0.2 liters per minute, a passing time of 40 minutes, and then kept warm for 2 hours. Finally, the MXene / silicon composite material was cooled to room temperature at a rate of 7°C per minute. The prepared MXene / silicon composite material was used to make electrodes according to the method of Example 1 and assembled into a simulated lithium-ion battery. The discharge capacity after 100 cycles at a current density of 100mA / g was close to 500mAh / g, which was significantly improved compared to the capacity of ordinary Ti3C2 MXene materials (~150mAh / g), and the cycle performance was good.

[0036] Example 3

[0037] Take 6g Nb2AlC powder (MAX) into a beaker, add 40mL HF (30%) solution, stir, and soak and etch for 36h at room temperature. Then centrifuge the etched Nb2C MXene powder, wash with deionized water to pH = 6-7, and freeze-dry in a freeze dryer for 24h. Stir 1g of dried Nb2CMXene powder in 50mL of an aqueous solution containing 0.05mol / L octadecyltrimethylammonium bromide (STAB) at 35°C for 24h. Then add 0.1mol / L nickel nitrate and stir at 35°C for 24h, wash with deionized water, and dry. The dried sample was placed in a CVD furnace, heated to 700°C at a rate of 5°C per minute under the protection of nitrogen, then kept warm for 4 hours to activate Ni metal, then cooled to 600°C and introduced a 120-minute silane and hydrogen mixed gas, with a volume ratio of 10%:90%, a flow rate of 0.5 liters per minute, an introduction time of 40 minutes, and then kept warm for 3 hours. Finally, it was cooled to room temperature at a rate of 10°C per minute to obtain a MXene / silicon composite material. The prepared MXene / silicon composite material was used to make electrodes according to the method of Example 1 and assembled into a simulated lithium-ion battery. The discharge capacity after 100 cycles at a current density of 100mA / g is close to 550mAh / g, which is significantly improved compared to the capacity of ordinary Nb2C MXene (~150mAh / g), and the cycle performance is good.

Claims

1. A method for preparing a MXene / silicon composite material, characterized in that: The preparation method comprises the following steps: (1) Taking MAX raw materials and treating them in a hydrofluoric acid solution to obtain MXene materials; (2) immersing the MXene material obtained in step (1) in a solution containing 0.001-20 g / mL of a cationic surfactant, stirring at 20-100° C. for 0.5-72 h, to obtain a MXene material solution intercalated with a cationic surfactant; (3) adding a metal soluble salt to the cationic surfactant intercalated MXene material solution obtained in step (2), stirring at 20-100° C. for 0.5-72 h, and then centrifuging, washing, and drying to obtain a metal intercalated MXene material; (4) The metal intercalation MXene material obtained in step (3) is heated to 300-1000°C at a rate of 1-10°C / min under a protective atmosphere, and kept warm for 0.1-12h to activate the metal and activate its catalytic effect, then cooled to 200-800°C, and a gas containing silane is introduced at a flow rate of 0.01-5L / min for 1-240min, and then kept warm for 0.1-12h, and finally cooled to room temperature at a rate of 1-20°C / min to obtain a MXene / silicon composite material.

2. The preparation method according to claim 1, characterized in that: In step (2), the cationic surfactant is one of dodecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, or a combination of any of them.

3. The preparation method according to claim 1 or 2, characterized in that: In step (2), the stirring is carried out at 30-80°C, preferably 30-65°C, more preferably 30-50°C, and the stirring time is 1-36h, preferably 3-24h, more preferably 10-24h.

4. The preparation method according to claim 1, characterized in that: In step (3), the metal soluble salt is a soluble salt containing at least one of the elements iron, cobalt, nickel, lead, copper, aluminum, antimony, manganese, tin, zinc, molybdenum, vanadium, zirconium and tungsten, and the soluble salt is a metal chloride, nitrate, sulfate or acetate.

5. The preparation method according to claim 1, characterized in that: The stirring in step (3) is carried out at 20-70°C, preferably 20-60°C, and the stirring time is 1-36h, preferably 5-24h.

6. The preparation method according to claim 1, characterized in that: In step (4), the silane-containing gas is a mixed gas of silane and other gases, and the other gases are one or a mixture of any of argon, nitrogen and hydrogen; in the silane-containing gas, the volume ratio of silane to other gases is 10-30%:90-70%, preferably 10-20%:90-80%.

7. The preparation method according to claim 1, characterized in that: In step (4), the metal intercalation MXene material is first heated to 400-1000°C at a rate of 2-8°C per minute under a protective atmosphere and kept warm for 1-12h to activate the metal and activate its catalytic performance. The temperature is preferably 400-900°C, more preferably 500-800°C, and the holding time is 1-8h, preferably 1-6h; then the temperature is lowered to 200-800°C, preferably 300-800°C, more preferably 400-700°C, and the flow rate of the silane-containing gas is 0 .01-5L / min, preferably 0.1-3L / min, more preferably 0.1-2L / min, the time for passing the silane-containing gas is 1-240min, preferably 1-180min, more preferably 1-120min, and then keep warm for 0.1-12h, preferably 0.1-10h, more preferably 0.5-6h, and finally cool to room temperature at a rate of 1-20℃ / min, preferably the cooling rate is 1-15℃ / min, more preferably the cooling rate is 1-10℃ / min.

8. The preparation method according to claim 1, characterized in that: The method for preparing the MXene / silicon composite material comprises steps (1) to (4).

9. A MXene / silicon composite material prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the MXene / silicon composite material as claimed in claim 9 as a negative electrode material for lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of MXene doped nanometer silicon particle negative electrode composite material and lithium ion battery containing composite material

    CN115513443A

  • Method for preparing silicon-carbon material through silane gas-phase in-situ compounding based on MXene carrier

    CN117923496A

  • Nanometer silicon coated SiOx / MXene composite negative electrode material and preparation method thereof

    CN118183749A